RELATIONSHIP BETWEEN LEADER INTEGRITY, RELIGIOSITY AND ISLAMIC WORK ETHICS: A CONCEPTUAL MODEL - Ali, Mohd Fauzwadi Mat; Ahmad, Muhammad (CENTRAL ASIA AND THE CAUCASUS, 2024)
This article seeks to develop the conceptual model on the relationship leader integrity, religiosity, and Islamic work ethics in a business organization. This article has introduced a theoretical framework of the relationship between leader integrity, religiosity, and Islamic work ethic.